Aktivitas Antioksidan Masker Peel-Off Kopi (Coffea arabica) dan Kunyit (Curcuma longa) Menggunakan Metode DPPH - Regia Desty Rakhmayanti; Youstiana Dwi Rusita (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Peel-Off face mask is one of the cosmetics that is used to treat skin from free radicals. Coffee (Coffea arabica) contains chlorogenic, ferulic, caffeic, and n-coumaric acids which can be useful as antioxidants. Turmeric (Curcuma longa) contains curcumin, which has anti-inflammatory and antioxidant properties. The purpose of this study is to evaluate the quality parameters and analyzed the antioxidant activity of peel-off masks containing coffee (Coffea arabica) and turmeric (Curcuma longa). This research has made 3 mask formulas, each of which contains coffee and turmeric. The formula made was a combination of coffee and turmeric with a ratio of each formula F1 (10:0), F2 (5:,5) and F3 (0:10). The result of organoleptic parameters for F1 was dark brown with coffee aroma and consistency like gel, F2 wasyellowish-brownn with spiced coffee aroma and consistency like gel and F3 was yellow with turmeric aroma and consistency like gel. The result of the homogeneity test of all formulasmula was homogeny. The result of the pH value of all formulasmula was 5. The resulspreadabilityd ability of F1, F2 and F3 were 26.877 cm2; 26.278 cm2; 26.875 cm2. The drying time of each formula was F1 27.36 min; F2 28.38 min; F3 28.54 min. The antioxidant activity is shown the by IC50 value. The value of IC50 for each formula F1 (37.277 ppm), F2 (34.757 ppm), and F3 (37.399 ppm). The test results showed that all formulas met the quality test requirements and had very strong antioxidant activity.